Grafen untuk Aplikasi Penyerapan Gelombang Radar Mikro: Dari Sintesis Graphene Oxide (GO) Berbasis Tempurung Kelapa - Yamin, Muthi'ah Alfiyah; Aritonang, Sovian; Murniati, Riri (Fakultas Teknik UMSU, 2024)
ABSTRACT Radar systems detect objects using electronic signals. Radar Absorbing Material (RAM), especially graphene, increases radar wave absorption. Using coconut waste to make Graphene Oxide (GO) supports sustainability. It advances more efficient and sustainable radar wave absorption technology. This research is based on literary analysis. The method used in this research is a literature review and in this study will compare the reflection loss material graphene oxide as a radar absorber with other materials. This research shows that GO synthesized with the Hummer method at 400°C has the best performance in radar wave absorption, competing with other materials such as CoTi1-xCexO3 and silicone rubber variations. This makes GO an attractive choice for radar wave absorption applications, especially on microwave frequencies.Keywords:Absorber Radar, Graphene Oxide, Coconut Waste, Hummer Method